What Happens in the Language Classroom in regards to Communication? An analysis of the Cooperative Principle (2018)
The concept of communication in the field of education has been discussed by language teachers, scholars, and researchers among others. This article analyzes and reflects on the way in which language teachers and students communicate in the language classroom. This analysis was done based on the rules of the Cooperative Principle, proposed by Paul Grice in 1975. The inquiry consisted on studying how the teacher and students flout the maxims of communication proposed by the principle (quality, quantity, relation and manner). For the analysis, an eighth grade English class at a private school was recorded, and parts of the video were extracted. This analysis is not focused on studying how teachers and students make mistakes, but rather how communication is carried out in the language classroom.